The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10689-016-9934-0
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the genotype–phenotype spectrum in hereditary colorectal cancer by gene panel testing

Abstract: Hereditary syndromes causing colorectal cancer include both polyposis and non-polyposis syndromes. Overlapping phenotypes between the syndromes have been recognized and this make targeted molecular testing for single genes less favorable, instead there is a gaining interest for multi-gene panel-based approaches detecting both SNVs, indels and CNVs in the same assay. We applied a panel including 19 CRC susceptibility genes to 91 individuals of six phenotypic subgroups. Targeted NGS-based sequencing of the whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 54 publications
2
48
0
1
Order By: Relevance
“…Germline point mutations and large deletions in the mothers against decapentaplegic homolog 4 (SMAD4) 44,131 and bone morphogenetic protein receptor type 1A (BMPR1A) 132 genes, underlie 40% to 60% of families with the JPS phenotype. 133 In addition, germline mutations in BMPR1A have been associated with a proportion of previously genetically unexplained familial or atypical adenomatous polyposis patients, 80 and a small proportion of patients meeting familial CRC type X (FCCTX) criteria, 134 thus expanding the phenotypic spectrum for this gene, and warranting its inclusion in multigene panels for CRC/polyposis testing. The diagnostic yield for patients with PJS and CS phenotypes is higher than JPS; up to 96% of individuals with PJS have an identified germline mutation in serine/threonine kinase 11 (STK11) 135,136 and approximately 80% of patients with CS have a mutation in the phosphatase and tensin homolog (PTEN) gene.…”
Section: Polyposis-associated Crc Risk Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…Germline point mutations and large deletions in the mothers against decapentaplegic homolog 4 (SMAD4) 44,131 and bone morphogenetic protein receptor type 1A (BMPR1A) 132 genes, underlie 40% to 60% of families with the JPS phenotype. 133 In addition, germline mutations in BMPR1A have been associated with a proportion of previously genetically unexplained familial or atypical adenomatous polyposis patients, 80 and a small proportion of patients meeting familial CRC type X (FCCTX) criteria, 134 thus expanding the phenotypic spectrum for this gene, and warranting its inclusion in multigene panels for CRC/polyposis testing. The diagnostic yield for patients with PJS and CS phenotypes is higher than JPS; up to 96% of individuals with PJS have an identified germline mutation in serine/threonine kinase 11 (STK11) 135,136 and approximately 80% of patients with CS have a mutation in the phosphatase and tensin homolog (PTEN) gene.…”
Section: Polyposis-associated Crc Risk Syndromesmentioning
confidence: 99%
“…Multigene panel testing for CRC has an increased clinical yield over iterative single gene or phenotype driven testing and is cost-effective. 6 The yield of moderate-to-high penetrance mutations from CRC gene panel testing Hereditary CRC and the Utility of Multigene Panel Testing e300 -Clinical Colorectal Cancer June 2018 has been reported to be 10% to 18% in differing CRC and polyposis cohorts 4,80,[171][172][173] but is dependent on the genes included on the panel. Importantly, to facilitate effective and appropriate clinical care and counseling, robust estimates of CRC risk are pivotal.…”
Section: Key Considerations In Crc Multigene Panel Testingmentioning
confidence: 99%
“…Data from Rohlin et al [22] confirmed overlapping phenotypes between different herditary CRC syndromes and the importance of using multigene panels. Authors applied a panel including 19 CRC susceptibility genes to 91 individuals of 6 phenotypic subgroups.…”
Section: Genetic Testing In Adenomatous Polyposis Syndromementioning
confidence: 93%
“…The mutational screening of MSH3 in our cohort did not identify any biallelic carriers. Two predicted deleterious variants were identified in heterozygosity in three unrelated patients: c.1394A>G (p.Y465C), located in the ATPase region of the MutS domain V (C‐terminal domain; Source: PFAM), and c.2732T>G (p.L911W) (Duraturo et al, ; Morak et al, ; Rohlin et al, ), affecting the MutS domain II (connector domain; Source: PFAM) and identified in two unrelated individuals (Table S1). Even if the two MSH3 variants are located in domains that play a critical role in MMR, their clinical significance is most probably inexistent in the absence of a second mutation in the other allele (Adam et al, ).…”
Section: Msh3 Biallelic Mutations Are Very Rare Among Unexplained Polmentioning
confidence: 99%